EFL learners’ views on learner autonomy and foreign language anxiety - Yukselir, Ceyhun; Ozer, Omer (LPPM Universitas Advent Indonesia, 2022)
This mixed-methods research explores the views of EFL learners about learner autonomy and foreign language classroom anxiety. The participants comprised of 126 EFL learners studying at two state universities in Turkey. In addition to the instruments developed by Chan et al. (2002) and by Horwitz et al. (1986), a semi-structured questionnaire was also employed to gain deeper insights of the participants’ understanding of autonomous learning and foreign language anxiety. The findings show that participants believed that they should have the ability to take responsibility for learning on their own. Regarding the question about classroom anxiety, participants accepted the anxiety induced by the fear of speaking, especially in real-life situations in front of people or with native speakers of English. Moreover, the data showed that 13 students felt highly anxious whereas 73 students were moderately anxious in their English classrooms. Thus, the current study has contributed to our understanding about LA and anxiety in terms of foreign language majors’ perceptions in the EFL context, roles and responsibilities, motivation and abilities, inside and outside classroom activities and the reasons which cause FLA.